BETA PADA PASAR BULLISH DAN BEARISH: STUDI EMPIRIS DI BURSA EFEK JAKARTA - Eduardus Tandelilin (Faculty of Economics and Business, Universitas Gadjah Mada, 2001)
This research is intended to empirically test the relationship between systematic risk of a stock, measured on the bullish market and bearish market with the return of stock in Indonesian Capital Market. Data used are monthly stock prices and market index acquired from JSX Monthly Statistic and Capital Market Book Directory Index, from January 1994 to December 1996. Samples in this research consist of 95 stocks chosen by applying purposive sampling method. Testing of the stocks’ beta is conducted toward portfolios of stocks’ beta on bullish and bearish market. Before testing, individual stocks’ betas are first corrected by utilizing Fowler and Rorke one lead and one lag correction method. The result shows an indication that portfolios of stocks’ beta on the two different markets can elaborate the portfolios’ returns significantly. This indication is derived from F values significant at confidence levels of 5% and 10%.